Multiple cotton wool spots following bone marrow transplantation for treatment of acute lymphatic leukaemia. Issue 5 (May 1985) - Gloor, B; Gratwohl, A; Hahn, H; Kretzschmar, S; Robert, Y; Speck, B; Daicker, B
Abstract : Three patients with acute lymphatic leukaemia developed visual impairment due to occlusion of small retinal vessels with multiple cotton wool spots after treatment which included whole body and skull irradiation followed by bone marrow transplantation and cyclosporin A. Withdrawal of cyclosporin A and treatment with corticosteroids was followed by recovery of visual acuity. This retinopathy and the retinal changes seen in the immunodeficiency syndrome are thought to be closely related. The possible role of cyclosporin A is discussed, though cotton wool spots and retinal haemorrhages have never been described in renal transplant patients during treatment with this drug. Withdrawal of cyclosporin A, which is highly effective in preventing graft-versus-host disease, can be fatal. Irradiation of the skull prior to bone marrow transplantation and intrathecal administration of methotrexate may be the most important factors causing the retinal ischaemic signs described here. The inclusion of an ophthalmologist in the team monitoring transplant patients would lead to increased documentation and a better understanding of this disease.